Feature-tracking cardiac magnetic resonance left ventricular global longitudinal strain improves 6 months after kidney transplantation associated with reverse remodeling, not myocardial tissue characteristics - Barbosa, Maurício Fregonesi [UNESP]; Contti, Mariana Moraes [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP]; Mauricio, Alejandra del Carmen Villanueva [UNESP]; Ribeiro, Sergio Marrone [UNESP]; Szarf, Gilberto (Springer Nature, 2021)
To determine whether left ventricular (LV) global longitudinal strain (GLS) measured by feature-tracking (FT) cardiac magnetic resonance (CMR) improves after kidney transplantation (KT) and to analyze associations between LV GLS, reverse remodeling and myocardial tissue characteristics. This is a prospective single-center cohort study of kidney transplant recipients who underwent two CMR examinations in a 3T scanner, including cines, tagging, T1 and T2 mapping. The baseline exam was done up to 10 days after transplantation and the follow-up after 6 months. Age and sex-matched healthy controls were also studied for comparison. A total of 44 patients [mean age 50 ± 11 years-old, 27 (61.4%) male] completed the two CMR exams. LV GLS improved from − 13.4% ± 3.0 at baseline to − 15.2% ± 2.7 at follow-up (p < 0.001), but remained impaired when compared with controls (− 17.7% ± 1.5, p = 0.007). We observed significant correlation between improvement in LV GLS with reductions of left ventricular mass index (r = 0.356, p = 0.018). Improvement in LV GLS paralleled improvements in LV stroke volume index (r = − 0.429, p = 0.004), ejection fraction (r = − 0.408, p = 0.006), global circumferential strain (r = 0.420, p = 0.004) and global radial strain (r = − 0.530, p = 0.002). There were no significant correlations between LV GLS, native T1 or T2 measurements (p > 0.05). In this study, we demonstrated that LV GLS measured by FT-CMR improves 6 months after KT in association with reverse remodeling, but not native T1 or T2 measurements.
Keywords: Cardiovascular magnetic resonance imaging; Native T1; Renal transplant; Strain; Subclinical cardiac dysfunction